GREEN ENERGY AND RATIONAL WATER RESOURCE MANAGEMENT AS ONE OF THE FIVE PRIORITY AREAS HIGHLIGHTED IN THE 2026 PRESIDENTIAL ADDRESS OF THE REPUBLIC OF UZBEKISTAN - Igor Kudryavsev (Modern American Journals, 2026)
This article analyzes green energy development and the rational use of water resources as one of the five priority areas outlined in the 2026 Address of the President of the Republic of Uzbekistan. In the context of global climate change, increasing water scarcity, and the transition to sustainable development models, the issues of renewable energy expansion and efficient water management have gained particular importance. The study examines the legal, institutional, and strategic foundations of state policy in the fields of green energy and water resource management, emphasizing their role in ensuring environmental security, economic stability, and social well-being. Special attention is paid to the integration of sustainable development principles into national legislation and public administration practices. The article concludes that the implementation of green energy initiatives and rational water use mechanisms is a key factor for achieving long-term sustainable development in Uzbekistan.
Keywords: Green energy; renewable energy sources; water resource management; rational use of water; sustainable development; environmental security; state policy; legal regulation; public governance; Uzbekistan